2014
DOI: 10.1108/meq-02-2013-0014
|View full text |Cite
|
Sign up to set email alerts
|

Strategic sustainability management and export performance

Abstract: Purpose -The purpose of this paper is to analyze the practices of strategic sustainability management and the main indicators of export performance in industrial companies of the rubber artifacts sector. Design/methodology/approach -The study characterizes itself as descriptive and quantitative and has had the intention to analyze the main practices of strategic sustainability management and the export performance indicators in companies of the artifacts and rubbers sector of the States of São Paulo and Rio Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Moreover, it was found that the implementation of sustainable practices such as the development of products and processes through technological innovation increased the level of exports (Rocha-Vencato et al, 2014). This is consistent with Staub, Kaynak and Gokc (2015), who recommend developing innovative strategies for sustainable performance, particularly with regard to the organization's identity.…”
Section: Benefitssupporting
confidence: 79%
“…Moreover, it was found that the implementation of sustainable practices such as the development of products and processes through technological innovation increased the level of exports (Rocha-Vencato et al, 2014). This is consistent with Staub, Kaynak and Gokc (2015), who recommend developing innovative strategies for sustainable performance, particularly with regard to the organization's identity.…”
Section: Benefitssupporting
confidence: 79%
“…A greater number of organizations than ever before have started focusing on the idea of sustainability as their natural process of the strategy being executed in order to make sustainability a routine matter of the organization [78]. Resultant social and environmental domains of sustainability also attracted the attention of researchers alongside the economic domain.…”
Section: Hypothesis 5 (H5) the Financial Perspective Positively Inflmentioning
confidence: 99%
“…Also, performance outcomes encourage organizations to fulfill their commitments towards environmental sustainability. In a nutshell, there is an opportunity for investigating the relationship between BSC and organizational performance with perspective to control and growth [94] and even to explore the relationship between organizational performance and environmental sustainability [64,78,95]. Figure 2 shows the research framework signifying the hypothesis postulated in order to understand the possible links among variables.…”
Section: Research Frameworkmentioning
confidence: 99%
“…As a result, more and more firms strive to internationalise their operations (da Rocha Vencato et al, 2014). Firms pursue internationalisation in order to, among other things, obtain the benefits of production at lower costs, reduce/diversify risk, and to widen their markets (Czinkota and Ronkainen, 2001).…”
Section: Introductionmentioning
confidence: 99%